2022
DOI: 10.3390/jcm11092346
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ramadan Participation with Psychological Parameters: A Cross-Sectional Study during the COVID-19 Pandemic in Iran

Abstract: COVID-19 restrictions are associated with poor physical-activity (PA). Less is known about the relationship between the combination of these restrictions with Ramadan intermittent fasting (RIF), PA, mental health, and sleep-quality. The present study aimed to evaluate whether COVID-19 restrictions and RIF during the fourth wave of the COVID-19 pandemic in Iran are associated with poor PA, anxiety, well-being, and sleep-quality outcomes. A total of 510 individuals participated in an online questionnaire that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…For first aim of the present study, as predicted, the results showed that all the measured indices were different before and during the pandemic, lower levels of physical activity and self-esteem and higher levels of social anxiety from before to during the COVID-19. The findings indicating detrimental effects of the COVID-19 pandemic on the levels of physical activity and of psychological indicators are in line with previous studies [ 6 , 15 , 29 31 , 33 , 34 ]. For example, Di Franco et al [ 10 ] in their study examined the effects of social distance on mental health status and physical activity during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For first aim of the present study, as predicted, the results showed that all the measured indices were different before and during the pandemic, lower levels of physical activity and self-esteem and higher levels of social anxiety from before to during the COVID-19. The findings indicating detrimental effects of the COVID-19 pandemic on the levels of physical activity and of psychological indicators are in line with previous studies [ 6 , 15 , 29 31 , 33 , 34 ]. For example, Di Franco et al [ 10 ] in their study examined the effects of social distance on mental health status and physical activity during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…However, others have shown that the pandemic has mainly affected the intensity of physical activity and not its frequency in Iran [ 32 ]. Since, research has also shown that physical activity is associated with decreased hospitalisation and can significantly reduce the mortality rates of patients with COVID-19 [Rahmati], and also considering that it has been determined, physical activity can bring many benefits, including improving the levels of well-being and sleep quality as well as reducing people anxiety [ 33 , 34 ]. Therefore, it is suggested that people, especially the older adults try to increase their resistance to various diseases, including COVID-19 pandemic, by increasing their level of physical activity throughout their lives [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether COVID-19 restrictions and RF during the fourth wave of the COVID-19 pandemic were associated with poor physical activity, anxiety, well-being, and sleep-quality outcomes were tested. 69 A total of 510 individuals participated in an online questionnaire disseminated to adults (!18 years) residing in Iran 3 days after the end of Ramadan 2021. Physical activity behavior, anxiety, well-being, and sleep quality were used.…”
Section: Infections and Inflammationsmentioning
confidence: 99%
“…Observers refrain from eating food, drinking liquids, and other physical needs such as smoking and sexual intercourse ( Ghram et al, 2021 ; Jahromi et al, 2014 ). Ramadan fasting (RF) as intermittent fasting is mandatory for all healthy adult Muslims ( Akbari et al., 2022 ; Lessan & Ali, 2019 ). Several studies have been conducted over the last decade to investigate the impact of RF on physiological performance ( Maughan et al, 2010 ; Zerguini et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%